Protective Effect of Ethanolic Mistletoe Leaves (Scurula atropurpurea (Bl.) Dans) Extract Against Protein Denaturation In Vitro - Aditiyarini, Dwi; Nadapdap, Christini Bernaindah; Restiani, Ratih (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Inflammation is a complex biological response that eliminates harmful stimuli, clears damaged tissues, and initiates healing. Protein denaturation is known to trigger inflammatory reactions and is associated with chronic disorders such as rheumatoid arthritis, lupus erythematosus, and serum sickness. Although steroidal and non-steroidal anti-inflammatory drugs (NSAIDs) are widely used, their long-term use may cause adverse effects. Herbal plants represent potential alternative therapies with fewer side effects. This study examined the anti-inflammatory potential of Scurrula atropurpurea, a hemiparasitic plant traditionally used for various medicinal purposes. The ethanolic leaf extract was evaluated for its phytochemical composition, antioxidant properties, and ability to inhibit egg albumin denaturation in vitro. Fresh leaves were collected from tea plants in Sapuran, Wonosobo, and extracted using Soxhlet with 96% ethanol. Phytochemical screening indicated the presence of alkaloids, flavonoids, tannins, phenolics, saponins, steroids, and terpenoids. Quantitative analysis showed a high total phenolic content (126.10 ± 1.5 mg GAE/g extract), moderate tannins, and relatively low flavonoids. The extract demonstrated weak antioxidant activity (IC50 = 140.4 ± 4.9 µg/mL) and minimal protein denaturation inhibition (maximum 1.51% at 100 ppm), significantly lower than sodium diclofenac as a positive control. Overall, the ethanolic extract of S. atropurpurea leaves exhibited low in vitro anti-inflammatory activity, suggesting the need for further investigation using alternative extraction methods, plant parts, or host species.